Dynamic response of land use and river nutrient concentration to long-term climatic changes - Bussi, Gianbattista; Janes, Victoria; Whitehead, Paul G.; Dadson, Simon J.; Holman, Ian P. (Elsevier, 2017)
The combined indirect and direct impacts of land use change and climate change on river water quality were assessed. A land use allocation model was used to evaluate the response of the catchment land use to long-term climatic changes. Its results were used to drive a water quality model and assess the impact of climatic alterations on freshwater nitrate and phosphorus concentrations. Climatic projections were employed to estimate the likelihood of such response. The River Thames catchment (UK) was used as a case-study. If land use is considered as static parameter, according to the model results, climate change alone should reduce the average nitrate concentration, although just by a small amount, by the 2050s in the Lower Thames, due to reduced runoff (and lower export of nitrate from agricultural soils) and increased instream denitrification, and should increase the average phosphorus concentration by 12% by the 2050s in the Lower Thames, due to a reduction of the effluent dilution capacity of the river flow. However, the results of this study also show that these long-term climatic alterations are likely to lead to a reduction in the arable land in the Thames, replaced by improved grassland, due to a decrease in agriculture profitability in the UK. Taking into account the dynamic co-evolution of land use with climate, the average nitrate concentration is expected to be decreased by around 6% by the 2050s in both the upper and the lower Thames, following the model results, and the average phosphorus concentration increased by 13% in the upper Thames and 5% in the lower Thames. On the long term (2080s), nitrate is expected to decrease by 9% and 8% (upper and lower Thames respectively) and phosphorus not to change in the upper thames and increase by 5% in the lower Thames.
Keywords: Water quality; Land use change; Scenario-neutral; INCA model; River Thames